Strategi Pertumbuhan Ekonomi Klungkung: Eksplorasi Potensi Bahari Nusa Penida - Sukarsa, Galuh Prabaningrum Ayu (Bali Membangun Bali: Jurnal Bappeda Litbang, 2025)
Purpose: Tourism plays an important role in the Balinese economy along with the development of various tourist destinations, including marine tourism in Nusa Penida, Klungkung Regency. This study aims to analyze the potential of leading sectors and explore the potential of Nusa Penida using the location quotient (LQ), dynamic location quotient (DLQ), and shift share approaches. Research methods: This study uses a quantitative method with secondary data sources to see the contribution of the economy to Bali Province sectorally. Data were obtained through literature studies from the websites of the Central Statistics Agency of Klungkung Regency and Bali Province, in addition to a number of books and research journals. Results and discussion: LQ analysis shows eight basic sectors, including the agricultural and manufacturing sectors. Meanwhile, DLQ analysis identifies twelve prospective sectors, such as manufacturing and financial services. The Shift Share approach finds nine sectors that are experiencing progressive growth, including the trade and education services sectors. Overall, the three leading sectors that emerged are: (1) water supply, waste management, and recycling; (2) information and communication; and (3) other services. Supporting sectors in marine tourism in Nusa Penida include accommodation and provision of food and beverages, as well as other services. Implication: Government intervention is crucial to improve the quality of the accommodation and provision of food and beverages sectors to support the development of marine tourism in Nusa Penida.